Estimation the Antibiotics Activity Against Vaginal Pathogenic Microorganisms in Pregnant Ladies with Early Rupture Membrane and their Fetal Outcome - Ban Amer Mousa1, Ehsan F. Hussein2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: The Preterm Labor: is the mean reason of the (80%) from the neonatal intrapartem, postpartum morbidity and mortality. Recently, vaginal infections have been related to high risks of PPROM and PROM. However, preterm labor and subsequent neonatal bad outcome can be avoid through several protective actions. Methods: This study was prepared through the period from January to December 2018 at Babylon Province, were for estimate the effect of vaginal infections in patients pregnant women with premature rupture membrane, the samples were 100 pregnant women, 50 were vaginal infected (as patients) and 50 were no(as controls). Results. Shows significant increasing of the fetal weight, while significant decreasing of the Maternal age and duration time in the patients, also elevation in the percentages of C/S and PROM in patients when comparing all these with controls. The pathogenic microorganisms; were CONS (coagulase negative staphylococcus auerus) are major insulated organism followed by Candida, and Bacteriod spp., and to less extent were Staph., Proteus and Bacteriod. The Cifixum, Ampicillin, Clotrimazol and Metronid were appropriate antibiotics used for treatment of the vaginal infections.